Q: What is p plus 3p plus 2q plus 5q?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

simply add the like terms: 4p -3p +2q -2q = p

Points: (p, q) and (7p, 3q) Midpoint: (4p, 2q) Slope: q/3p Perpendicular slope: -3p/q Perpendicular bisector equation:- => y-2q = -3p/q(x-4p) => qy-2q^2 = -3p(x-4p) => qy-2q^2 = -3px+12p^2 => qy = -3px+12p^2+2q^2 In its general form: 3px+qy-12p^2-2q^2 = 0

3p

3

7p+5q=-3, p=1 7Xp+5q=-3 7+5q=-3 5p=-10 p=-2

Related questions

simply add the like terms: 4p -3p +2q -2q = p

Let f(X)=2X2+6X+3 So f(-p)=f(2q) or 2p2-6p+3=8q2+12q+3 or p2-3p=4q2+6q or p2-4q2=3p+6q or (p+2q)(p-2q)=3(p+2q) so p-2q=3

10p and 14q or 2(5p + 7q)

Points: (p, q) and (7p, 3q) Midpoint: (4p, 2q) Slope: q/3p Perpendicular slope: -3p/q Perpendicular bisector equation:- => y-2q = -3p/q(x-4p) => qy-2q^2 = -3p(x-4p) => qy-2q^2 = -3px+12p^2 => qy = -3px+12p^2+2q^2 In its general form: 3px+qy-12p^2-2q^2 = 0

3p

3

7p+5q=-3, p=1 7Xp+5q=-3 7+5q=-3 5p=-10 p=-2

3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7

3q + 2p

-(b + c - p - 2q)(b + c + p + 2q)

-5 + 3p - p = -5 + 2p

p2 + 3p = p (p + 3)